2017
DOI: 10.1073/pnas.1616417114
|View full text |Cite
|
Sign up to set email alerts
|

Pre/pro-B cells generate macrophage populations during homeostasis and inflammation

Abstract: Most tissue-resident macrophages (Mφs) are believed to be derived prenatally and are assumed to maintain themselves throughout life by self-proliferation. However, in adult mice we identified a progenitor within bone marrow, early pro-B cell/fraction B, that differentiates into tissue Mφs. These Mφ precursors have non-rearranged B-cell receptor genes and coexpress myeloid (GR1, CD11b, and CD16/32) and lymphoid (B220 and CD19) lineage markers. During steady state, these precursors exit bone marrow, losing Gr1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 40 publications
2
38
1
Order By: Relevance
“…An alternative mechanism for the replenishment of serous cavity F4/80 hi macrophages has been proposed recently. Audzevich et al [45] have suggested that macrophages can also arise from pre/pro-B cells in both peritoneal and pleural cavities. By using the Mb1 iCre .Rosa26 LSL-eYFP strain to fate-map B cell progenitors, high levels of labelling were detected in peritoneal and pleural macrophages, but not in most other tissue macrophages under steady state conditions.…”
Section: The Ontogeny Of Serous Cavity Macrophagesmentioning
confidence: 99%
“…An alternative mechanism for the replenishment of serous cavity F4/80 hi macrophages has been proposed recently. Audzevich et al [45] have suggested that macrophages can also arise from pre/pro-B cells in both peritoneal and pleural cavities. By using the Mb1 iCre .Rosa26 LSL-eYFP strain to fate-map B cell progenitors, high levels of labelling were detected in peritoneal and pleural macrophages, but not in most other tissue macrophages under steady state conditions.…”
Section: The Ontogeny Of Serous Cavity Macrophagesmentioning
confidence: 99%
“…Recently, another bone marrow-derived source of adult macrophage progenitors has been discovered (Audzevich et al, 2017 ). These cells are bi-phenotypic early pro-B cells that express both myeloid and lymphoid markers.…”
Section: Origins Of Tissue-resident Macrophagesmentioning
confidence: 99%
“…These cells are bi-phenotypic early pro-B cells that express both myeloid and lymphoid markers. Like HSC-derived monocytes, early pro-B cells exit the bone marrow, travel through the circulation, and contribute to certain tissue-resident macrophage populations (such as in the peritoneum, pleural cavity, and intestine) during tissue homeostasis and inflammation (Audzevich et al, 2017 ).…”
Section: Origins Of Tissue-resident Macrophagesmentioning
confidence: 99%
“… 91 , 92 However, subsequent findings suggest that this may be too simplistic and that more pro-inflammatory as well as pro-regenerative macrophage subsets may exist and that differentiation of these is governed by their local microenvironment. 89 , 101 It is becoming clear that macrophage subtypes have vital and somewhat contradictory roles during tissue repair and that the careful balance of these different phenotypic states will be crucial for allowing full tissue regeneration. 16 , 51 , 54 , 55 , 87 90 , 96 , 100 , 102 – 104 Macrophage subsets have recently been identified in zebrafish 105 and suggested to contribute to aspects of larval fin regeneration and wound angiogenesis (see section 'Re-vascularisation' below), 106 , 107 but further investigation will be required to determine the origin of these different subtypes and if pro-regenerative populations are enriched following skin or cardiac injury in fish, contributing to the regenerative capacity of these organs.…”
Section: The Inflammatory Responsementioning
confidence: 99%